Characterization of post-vaccination SARS-CoV-2 T cell subtypes in patients with different hematologic malignancies and treatments - Pfannes, Roald; Pierzchalski, Arkadiusz; Maddalon, Ambra; Simion, Alexandra; Zouboulis, Christos C.; Behre, Gerhard; Zenclussen, Ana Claudia; Westphal, Sabine; Fest, Stefan; Herberth, Gunda (Frontiers in Immunology, 2023)
To evaluate the benefits of SARS-CoV-2 vaccination in tumor patients it is relevant to understand immune responses elicited after vaccination. Patients affected by hematologic malignancies are frequently immune-compromised and show a decreased seroconversion rate compared to other cancer patients or controls. Therefore, vaccine-induced cellular immune responses in these patients might have an important protective role and need a detailed evaluation. In our study certain T cell subtypes (CD4, CD8, Tfh, T), including cell functionality indicated by cytokine secretion (IFN, TNF) and expression of activation markers (CD69, CD154) were assessed via multi-parameter flow cytometry in hematologic malignancy patients (N=12) and healthy controls (N=12) after second SARS-CoV-2 vaccine dose. PBMC of post-vaccination samples were stimulated with a spike-peptide pool (S-Peptides) of SARS-CoV-2, with CD3/CD28, with a pool of peptides from Cytomegalovirus, Epstein-Barr virus and Influenza A virus (CEF-Peptides) or left unstimulated. Furthermore, the concentration of spike-specific antibodies has been analyzed in patients. Our results indicate that hematologic malignancy patients developed a robust cellular immune response to SARS-CoV-2 vaccination comparable to that of healthy controls, and for certain T cell subtypes even higher. The most reactive T cells to SARS-CoV-2 spike-peptides belonged to the CD4 and Tfh cell compartment. In this regard the immunomodulatory treatment of patients before the vaccination period seems to be of importance as it was strongly associated with a higher percentage of activated CD4 and Tfh cells. SARS-CoV-2- and CEF-specific T cell responses significantly correlated with each other. Compared to lymphoma, myeloma patients had an increased percentage of SARS-CoV-2 specific Tfh cells. T-SNE analysis revealed higher frequencies of T cells in patients, especially in myeloma patients, compared to controls. In general, after vaccination, SARS-CoV-2 specific T cells were also detectable in patients without seroconversion. Concluding, hematologic malignancy patients are capable to develop a SARS-CoV-2 specific CD4 and Tfh cellular immune response after vaccination and certain immunomodulatory therapies in the period before vaccination might increase the antigen-specific immune response. A proper response to recall antigens reflects immune cellular functionality and might be predictive for the generation of a newly induced antigen-specific immune response as it is expected after SARS-CoV-2 vaccination.